Mass spectrometric study of selected precursors and degradation products of chemical warfare agents - Papousková, Barbora; Bednár, Petr; Frysová, Iveta; Stýskala, Jakub; Hlavác, Jan; Barták, Petr; Ulrichová, Jitka; Jirkovský, Jaromír; Lemr, Karel (Journal of mass spectrometry, 2007)
Selected precursors and degradation products of chemical warfare agents namely N,N-dialkylaminoethane-2-ols, N,N-dialkylaminoethyl-2-chlorides and some of related N-quaternary salts were studied by means of electrospray ionization-multiple tandem mass spectrometry (ESI-MS(n)). Proposed structures were confirmed with accurate mass measurement. General fragmentation patterns of these compounds are discussed in detail and suggested processes are confirmed using deuterated standards. The typical processes are elimination of alkene, hydrogen chloride, or water, respectively. Besides, elimination of ethene from propyl chain under specific conditions was observed and unambiguously confirmed using exact mass measurement and labelled standard. The potential of mass spectrometry to distinguish the positional isomers occurring among the studied compounds is reviewed in detail using two different MS instruments (i.e. ion trap and hybrid quadrupole-time of flight (Q-TOF) analyzer). A new microcolumn liquid chromatography (microLC)/MS(n) method was designed for the cases where the resolution based solely on differences in fragmentation is not sufficient. Low retention of the derivatives on reversed phase (RP) was overcome by using addition of less typical ion pairing agent (1 mM/l, 3,5-dinitrobenzoic acid) to the mobile phase (mixture water : acetonitrile).
Keywords: Indicators and Reagents; Gas Chromatography-Mass Spectrometry; Chemical Warfare Agents; isomerie; roztoky; hmotnostní spektrometrie s elektrosprejovou ionizací; chemické bojové látky; Chromatography, Liquid; Isomerism; chromatografie kapalinová; plynová chromatografie s hmotnostně spektrometrickou detekcí; Spectrometry, Mass, Electrospray Ionization; Solutions; indikátory a reagencie